Susac's syndrome: Leptomeningeal enhancement on 3D FLAIR MRI. (June 2016) - Engisch, Renate; Titelbaum, David S; Chilver-Stainer, Lara; Kellner-Weldon, Frauke
Background: Contrast-enhanced (ce) fluid-attenuated inversion recovery magnetic resonance imaging (FLAIR MRI) has recently been shown to identify leptomeningeal pathology in multiple sclerosis. Objective: To demonstrate leptomeningeal enhancement on three-dimensional (3D) FLAIR in a case of Susac's syndrome. Methods: Leptomeningeal enhancement was correlated with clinical activity over 20 months and compared to retinal fluorescein angiography. Results: The size, number, and location of leptomeningeal enhancement varied over time and generally correlated with symptom severity. The appearance was remarkably similar to that of retinal vasculopathy. Conclusion: Ce 3D FLAIR may aid in diagnosis and understanding of pathophysiology in Susac's syndrome and may serve as a biomarker for disease activity.